In Vitro Mutagenesis of Etlingera elatior by Gamma Ray Intermittent Irradiation - Azzahra, Elmi Irmayanti; Aisyah, Syarifah Iis; Dinarti, Diny; Krisantini, Krisantini (Journal of Tropical Crop Science, 2018)
Etlingera elatior is tropical ornamental plant commonly called “torch ginger” from Zingiberaceae family. Conventional breeding of E. elatior is limited by cross incompatibility, poor fruit set and low seed production.  In this study irradiation of E. elatior with Gamma ray performed to induce mutation. This study was aimed to increase morphological diversity and to obtain unique morphological characters to increase the aesthetic value of E. elatior as ornamental plants and cut flower. Two genotypes of E. elatior, red and white flowers, were tested. The LD20, LD35, and LD50 were determined following intermittent (split dose) Gamma irradiation with a two-hour gap between each gamma ray shot. Red genotype E. elatior explants were irradiated with dose of 3 + 3 Gy (LD20); 4 + 4 Gy (LD35) and 5 + 5 Gy (LD50); white genotype were irradiated with a dose of 2 + 2 Gy (LD20); 2.8 + 2.8 Gy (LD35) and 3.7 + 3.7 Gy (LD50). Non-irradiated explants were set as control.  The results of this study indicated that the increase in dose of gamma ray irradiation changed shoot length and number of leaves in the red genotype per explant as compared to control. Morphological changes occurred in leaf shape at 5 + 5 Gy and 3.7 + 3.7 Gy and formation of variegated leaves at 2.8 + 2.8 Gy and 5 + 5 Gy. Keywords: mutation breeding, ornamental plant, split irradiation dose, torch ginger, Zingiberaceae